THE EFFECT OF SERVICE EXCELLENCE ON PATIENT SATISFACTION IN THE OUTPATIENT ROOM OF GAMBIRAN HOSPITAL, KEDIRI CITY - Sekar Rochmah Ningtyas; Amarin Yudhana (Universitas STRADA Indonesia, 2025)
The increasing need for quality health services and the increasingly fierce competition between hospitals in the era of globalization are critical factors for patient satisfaction and trust, so there is a need to improve the quality of services. The purpose of this study is to identify the influence of service excellence on patient satisfaction in road drainage installations. This type of research is a quantitative research of a cross sectional approach. The sample used was 54 new outpatients who were calculated using Gpower software with purposive sampling technique. The dependent variable in this study is patient satisfaction, while the independent variable is service excellence. Data was collected through the distribution of questionnaires and then analyzed using the Simple Linear Regression Test. The results of the study show that there is a significant influence between service excellence and patient satisfaction. It is important that employees have the knowledge and awareness to always provide excellent service and increase the speed of response and accuracy in providing medical information and services.